Black Phosphorous: Nanoscopy of Black Phosphorus Degradation (Adv. Mater. Interfaces 12/2016). Issue 12 (June 2016) - Gamage, Sampath; Li, Zhen; Yakovlev, Vladislav S.; Lewis, Colin; Wang, Han; Cronin, Stephen B.; Abate, Yohannes
Abstract : The ambient degradation of exfoliated black phosphorous with and without a thin Al2 O3 coating layer is investigated by Sampath Gamage, Yohannes Abate, and co‐workers in article 1000121. Supported by computational modeling, it is found that the thickness and quality of coating are critical to effectively passivate black phosphorous from ambient degradation. Oxidized phosphorus species can still form underneath 5 nm or less thick Al2 O3 coating, which renders thin coatings insufficient to protect BP against degradation.